Development and Influencing Factors of International Trade in Digitally Deliverable Services - Di, Yuna; Zhi, Ruixin; Song, Huaixi; Zhang, Lu (Frontiers in Psychology, 2022)
Introduction: International trade in digitally deliverable services has been developing rapidly in recent years, especially during pandemics. However, the growth rate and scale differ among regions and countries. To promote the growth and bridge the divide of global trade in digitally deliverable services, we provide feasible policy suggestions in this paper. Methods: Based on panel data of 33 countries’ digitally deliverable service trade from 2005 to 2020, this study analyzes the development trends and influencing factors of international trade in digital-global service trade. Results: The development of digitally deliverable services in developed countries is far ahead, while in emerging economies such as China and India, it is growing at a high speed. Digital infrastructure, human capital and innovation capacity have a significant impact on the digitally deliverable trade of countries with the level of STI playing the most important influence. Further, heterogeneity analysis shows that human capital and STI capacity are more sensitive to the digitally deliverable trade of middle-income countries than to the impact of high-income countries, and the contribution of population in middle-income countries is more pronounced. Conclusion: As the proportion of digital trade in global trade continues to increase, the role of digital service trade in countries’ sustainable development is becoming more prominent. To cope with such opportunities and challenges, countries, especially developing countries, should actively increase digital infrastructure construction, improve talent training, vigorously develop digital technology, and enhance their innovation capacity.